The Effectiveness of the Marketing Mix Used by Penshoppe in Terms of Product, Price, Place, and Promotion: A Literature Review - Ramos, John Karl De Guzman (JPAIR Multidisciplinary Research, 2025)
This study scrutinizes and examines Penshoppe’s expansion and strategic growth as a fashion retail company. The company was founded in Cebu, Philippines. Bernie Liu founded the small t-shirt printing business in 1986 as a venture. That was the beginning of Penshoppe, and then it steadily developed into a well-known domestic and global brand. The research examines Penshoppe’s application of the Marketing Mix Framework, which encompasses Price, Product, Place, and Promotion, to address market changes, competitive pressures, and industry interactions. By combining theoretical frameworks with real-world brand tactics, the study emphasizes the importance of aligning marketing initiatives with consumer preferences and adapting to external market circumstances. It also examines the challenges Penshoppe has faced in expanding internationally. The market’s harsh environment and how these encounters shaped its strategy for worldwide branding. The results reveal that the Marketing Mix remains a useful strategic tool; however, its effectiveness depends on how well it is tailored to a particular market condition.